1989
DOI: 10.3109/00365548909021694
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Tetanus in Finland from 1969 to 1985

Abstract: During the period 1969-85, tetanus caused the hospitalization of 106 patients (63 men and 43 women) in Finland. 12 (11.3%) of them died, most of the causes of death being unexpected complications during the intensive care. The majority of the patients were more than 50 years old and had not been fully vaccinated against tetanus. There was a clear seasonal variation, most of the cases occurring during the months when there is no snow on the ground. Half of the primary lesions were minor injuries to hands and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Of persons returning to work after contracting tetanus, one study found 13% were out of work less than 1 month, 57% were out of work 1 to 3 months, and 26% were out of work greater than 3 months (Luisto, 1992). In a previous study (Luisto 1980), tetanus survivors were found to be at higher risk for subsequent muscular fatigue and cramps, nervousness, decreased mental functioning, difficulties with balance, speech and memory, development of palsies, muscular atrophy, and reduced tendon reflexes. When tetanus occurs, the risk of death is substantial.…”
Section: Rationale For Treatment Vs Prevention Costsmentioning
confidence: 92%
“…Of persons returning to work after contracting tetanus, one study found 13% were out of work less than 1 month, 57% were out of work 1 to 3 months, and 26% were out of work greater than 3 months (Luisto, 1992). In a previous study (Luisto 1980), tetanus survivors were found to be at higher risk for subsequent muscular fatigue and cramps, nervousness, decreased mental functioning, difficulties with balance, speech and memory, development of palsies, muscular atrophy, and reduced tendon reflexes. When tetanus occurs, the risk of death is substantial.…”
Section: Rationale For Treatment Vs Prevention Costsmentioning
confidence: 92%
“…Altogether 106 cases of tetanus were found (mean 6.2 cases/year). There were 63 men and 43 women, and their ages ranged from 5 to 92 (mean 49.7, SD 18.0) year s; 12 patients (11.3070) died (11 For 100 patients a primary lesion leading to tetanus was identified . The records of these patients were analyzed regarding occupational accidents compensated by an insurance company.…”
Section: Methodsmentioning
confidence: 99%
“…Its incidence decreases, and the cases of tetanus are often caused by mino r injuries (3). Although the epidemiology of tetanus in developed countries has been thoroughly examined (4)(5)(6)(7)(8)(9)(10)(11), very little is known of tetanus as a complication of occupational accidents. Because of the occurrence of tetanus spores in the environment, the farming population has been suspected to be especially at risk of tetanus.…”
mentioning
confidence: 99%
“…Solid waste workers are also prone to puncture injuries further demonstrating the evidence for an infectious pathway for tetanus. Seven of the studies reported an age-related decrease in tetanus immunity (Bizzini et al 1978, Simonsen et al 1984, Matzkin et al 1985, Carducci et al 1987, Cellesi et al 1988, Luisto 1989, Holland & Carruth 2001.…”
Section: Waste Management and Researchmentioning
confidence: 99%